IMPORTANCE OF EDUCATIONAL TECHNOLOGIES AND METHODS OF USE IN IMPROVING SPEAKING SKILLS OF ENGLISH LANGUAGE LEARNERS (Web of Teachers: Inderscience Research, 2024)
This article introduces students to communication, ability, language acquisition, ability to concentrate, creativity, innovation, artistic and cultural connections, self-management, persistence, initiative, decision-making ability and flexibility are covered. In the article, through cultural competence, the use of cultural resources that are already accepted in society, but contain potential opportunities processes are analyzed.